Estudo das propriedades eletrônicas e estruturais de defeitos topológicos e fronteiras de grão em grafeno primeiros princípios - Joice da Silva Araujo (2011)
In this thesis, we perform first-principles calculations, based on the Kohn-Sham formulation of density functional theory, within the pseudopotential approximation, to investigate the energetics and the electronic and structural properties of polycrystalline grapheneand graphene containing topological defects. The work is motivated by the fact that, presently, grain boundaries and topological defects are topics of prominence in the physics of graphene obtained via chemical reduction of graphene oxide or via chemical vapor deposition technique.The thesis is comprised of four interrelated studies. In the first work, we consider tilt grain boundaries in graphene for three different values of the tilt angle between adjacent grains. The geometry of the boundary is formed by a periodic succession of pentagon-heptagon pairs, which is the structural model proposed for a grain boundary observed via scanning tunneling microscopy, on the surface of Highly Oriented Pyrolytic Graphite (HOPG) in 2002. Our calculations indicate that the formation energy behaves nonmonotonically with the tilt angle and also the generation of a anisotropic Dirac cone at the Fermi level at ak-point that lies along the boundary direction in the Brillouin zone.In the second work, we investigate the possibility that the magnetism observed experimentally in a grain boundary on the surface of HOPG sample can be due to vacancies in the grain boundary core. Our calculations show that vacancies in grain boundaries in grapheneintroduce localized states at the Fermi level, with instabilities leading to magnetic states, and also that vacancies are more favorably formed in the grain boundary core, mostly in compression regions of the defect.In the third work, we consider planar and corrugated graphene sheets with different concentrations of pentagonal and heptagonal carbon rings to study the corrugation effects in the stability and electronic properties of defective graphene sheets. Our results indicate the full variety of single-particle electronic including genuine metals, graphenelike nullgap semiconductors, and also finite-gap semiconductors. Generally, corrugation tends to reduce the DOS at Fermi level, to widen the gap, or even lead to gap opening in some cases where the parent planar geometry is metallic. Our calculations also indicate an instabilityof planar geometries when the topological defect concentration is smaller that a critical value, because five and seven-membered carbon rings develop positive and negative local curvature fields, respectively, in order to preserve the tri-coordination of each carbon atom in the sheet.In the last work, we study the effect of compressive deformations and holes in graphene, graphane, and graphenol sheets with a high initial concentration of dissociated pentagonheptagon pairs. We find that, upon relaxation, topological defects tend to cluster in a rich variety of morphological patterns, with morphological features that depend of the nature of the initial strain imposed on the system. Many of these topological-defect clusters have low formation energies, upon strain relaxation. The results are in excellent agreement with the patterns observed recently in samples of reduced graphene oxide that have largeareas with topological defect clusters.